Biofilm-forming vaginal lactobacilli inhibit Escherichia coli isolated from women with urinary infections - Leccese Terraf, Maria Cecilia (2014)
Lactobacilli are the dominant microorganisms of the healthy human vagina and participate in the maintenance of the ecological balance of the urogenital tract. They can inhibit the growth of urogenital pathogens by different mechanisms. The intravaginal administration of beneficial lactobacilli in pharmaceutical products has been proposed to restore the vaginal microbiome. The biofilm formation of lactobacilli is a beneficial characteristic to favor their mucosal colonization and/or permanence. In this study, the virulence factors of clinical Escherichia coli isolates and the inhibitory ability of biofilm-forming vaginal lactobacilli against this uropathogen were evaluated. The resistance of E. coli 36 and 36a (isolated from a patient with pyelonephritis) and E. coli 275 (isolated from a patient with recurrent cystitis) to different antibiotics (determined by disc diffusion method, according to Clinical and Laboratory Clinical Institute recommendations) and the presence of virulence genes (by multiplex PCR) were assayed. Antimicrobial activity of vaginal Lactobacillus rhamnosus CRL1332, Lactobacillus reuteri CRL1324 and Lactobacillus gasseri CRL 1263 was assayed using the agar plate diffusion technique. Lactobacillus supernatant aliquots were assayed, untreated, neutralized with NaOH or neutralized and treated with catalase. E. coli 36 and 36a were susceptible to all the antibiotics tested, while E. coli 275 resulted an ESBL (extended-spectrum-beta-lactamase)-producing strain. In E. coli 36 and 36a, fimH, papAH (adhesins), fyuA (siderophore), traT (serum resistance) and kpsMTII (capsule) genes were detected. In E. coli 275, fimH, fyuA, traT and agn43 (biofilm formation) genes were evidenced. L. reuteri CRL1324 and L. rhamnosus CRL1332 were able to inhibit the growth of the three E. coli strains. The inhibitory activity against E. coli disappeared after the supernatant neutralization, indicating that organic acids are responsible of the antagonism. The Lactobacillus strains evaluated are promising probiotic candidates to prevent or treat urinary infections caused by E. coli.